(untitled) (Medical Forum Monthly, 2020)
Objective: To compare bupivacaine alone versus bupivacaine plus fentanyl during labour in terms of mean pain score. Study Design: Double Blind Randomized controlled trial study. Place and Duration of Study: This study was conducted at the Department of Anesthesia, PIC, Lahore and GMC, Gujranwala from July 2018 to December 2018. Materials and Methods: Before conduct of study informed consent from patient and permission from institutional ethical review committee was taken. On the basis of random numbers patients were divided into two different groups. The study group designated as group- A received bupivacaine 0.1%±2 mcg/ml fentanyl in 10 ml normal saline while the control group designated as Group-II received bupivacaine 0.125% alone. Visual Analogue Scale was used to assess the pain score during labour, where score of 10-30 was taken as mild whereas 30-60 and 60-100 were considered as moderate and severe pain respectively. Results: A total of 80 patients divided into two equal groups were included in this study. The study results showed that in Group-I total of 31 patients (77.5%) were 20-28 years of age and 9 (22.5%) 29-35 years of age as compared to group B where 29 patients (72.5%) were 20-28 years of age and 11 patients (27.5%) of age 29-35 years. In Group-I mean ± standard deviation was 28.73±2.88 years whereas Group-II it was 29.35±3.00 years. Mean of gestational age in Group-I and mean parity was calculated as 39.48±1.09 weeks and 2.68±1.16 paras while in Group-II it was 39.18±1.08 weeks and 2.45±0.96 paras respectively. Comparison of bupivacaine alone versus bupivacaine plus fentanyl during labour in terms of mean pain score was recorded in Group-I as 1.32+0.47 and in Group-II as 18.22+2.32. A significant difference was shown by a P value of 0.00. Conclusion: We concluded that mean pain score is significantly reduced in bupivacaine plus fentanyl when compared with bupivacaine alone during labour in terms of mean pain score.